2006
DOI: 10.2190/r80g-580x-x1h2-6936
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Associated Factors among Adults with Epilepsy in Nigeria

Abstract: Controlling seizures and paying attention to the psychological needs of adult epileptics will have a positive effect on the QOL among Nigerian epileptics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 37 publications
6
32
0
1
Order By: Relevance
“…Eight studies reported no association between employment and HRQoL. Of these, four had sample sizes <115 and, therefore, low statistical power (Loring et al., 2004; Thomas et al., 2005; Meldolesi et al., 2006; Mosaku et al., 2006; Zhao et al., 2008). Other demographic factors (e.g., socioeconomic status, financial income) were evaluated in only a few studies and, therefore, there is insufficient information to comment on their associative status with HRQoL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported no association between employment and HRQoL. Of these, four had sample sizes <115 and, therefore, low statistical power (Loring et al., 2004; Thomas et al., 2005; Meldolesi et al., 2006; Mosaku et al., 2006; Zhao et al., 2008). Other demographic factors (e.g., socioeconomic status, financial income) were evaluated in only a few studies and, therefore, there is insufficient information to comment on their associative status with HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…Ten others reported no association. Of these, five studies (Loring et al., 2004; Meldolesi et al., 2006; Mosaku et al., 2006; Zhao et al., 2008; Phabphal et al., 2009) had a sample size ranging from 37–106 and, therefore, low statistical power to detect an association between educational level and HRQoL. Six studies showed unemployment to be associated with poorer HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…The social, economic and health impact of mental illness are far-reaching, where they are associated with excess all-cause mortality [2-4], work related disability [2, 4-6]. lower quality of life [7] and cardiovascular diseases risk [8-10]. Studies conducted in sub-Saharan Africa show that 20–30% of primary health clinic attendees present with depressive symptoms and other psychological disorders as the first or secondary reason for seeking medical care [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore a limited measure of disability in the narrower sense of this term, in that persons with disability can often be asymptomatic. It is best understood in this context as a measure of emotional distress (Ogundipe et al, 2014) or a proxy for quality of life (Mosaku et al, 2006), as it has been used in other African studies. Future research of this kind could employ the WHODAS 2.0 (World Health Organization, 2010), which focuses specifically on disability and has been used to generate utility scores for QALYs.…”
Section: Discussionmentioning
confidence: 99%